Pengaruh Latihan Calf Raises Terhadap Keakuratan Long Pass dalam Permainan Sepak Bola Pada Klub Blofour FC (U-12) - Hidayat, Wadi; Sudirjo, Encep; Dinangsit, Dinar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of calf raises training on long pass accuracy in soccer games for U-12 players of Blofour FC Club. This study used a quantitative approach with a one-group pretest–posttest experimental design. The study sample consisted of 20 players aged 10–12 years who participated in a calf raises training program for four weeks with a frequency of twice per week (a total of eight meetings). The instrument used was a long pass accuracy test that has been declared valid and reliable. Data analysis was carried out through normality tests, homogeneity tests, and paired sample t-tests. The results showed that the average pretest score of 26.90 increased to 35.45 in the posttest, with an average increase of 8.55 points. The results of the paired sample t-test showed a calculated t value of 15.15 with a significance value of p = 0.000 (p < 0.05), which indicates a significant difference between the pretest and posttest results. Based on these results, it can be concluded that calf raises significantly improved long pass accuracy in U-12 soccer players at Blofour FC. Keywords: Calf Raises, Long Pass Accuracy, Muscle Strength Training, Soccer, Young Players.